Optimization of geometry forms for wind mill mouth of the “rotor-in-socket” type - Vladimir A. Kostyukov; Mikhail Yu. Medvedev; Andrey N. Maevskiy; Nikolay K. Poluyanovich; Vasily V. Savchenko (Advanced Engineering Research, 2017)
Introduction. The method and results of the aerodynamic research of the vertical axis wind power plants (WPP) with an axisymmetric stator are considered. The work objective is to show the application perspectiveness of vertical axis wind-power plants of the specified type for the national economy. Materials and Methods. The technique of virtual aerodynamic blasting and the corresponding design optimization at the specified criterion are used to perform the tasks. Within the framework of this technique, numerical aerodynamic analysis of a single rotor of the given type, and of the “rotor + socket” system before and after the optimization at the specified parameters of the freestream and rotor spinning is performed. When comparing the power of the obtained optimized WPP design with analogs, other things being equal, the aerodynamic similarity method is used. Research Results. Representative patterns of the aerodynamic flow around the investigated WPP type are obtained before and after the optimization. The distinctive distributions of the scalar and vector fields at the given parameters of the freestream and rotor spinning are studied. Dependent graphs are plotted against the linear freestream velocity for the projections of the rotor shaft moment (with WPP standard and optimized forms), as well as for the corresponding useful and side powers. A comparison of the power of the optimized WPP under consideration, and analogues, other factors being equal, is made. Discussion and Conclusions. The application perspectiveness of the vertical axis wind turbines with an axisymmetric stator designed to create useful interference with the rotor in order to increase useful shaft power is shown. Such wind power plants meet and exceed, at any rate upon the average, the corresponding classical vertical axis structures.